Dual localized mitochondrial and nuclear proteins as gene expression regulators in plants? - Giegé, Philippe; Duchêne, Anne-Marie (Frontiers in Plant Science, 2012)
Mitochondria heavily depend on the coordinated expression of both mitochondrial and nuclear genomes because some of their most significant activities are held by multi-subunit complexes composed of both mitochondrial and nuclear encoded proteins. Thus, precise communication and signaling pathways are believed to exist between the two compartments. Proteins dual localized to both mitochondria and the nucleus make excellent candidates for a potential involvement in the envisaged communication. Here, we review the identified instances of dual localized nucleo-mitochondrial proteins with an emphasis on plant proteins and discuss their functions, which are seemingly mostly related to gene expression regulation. We discuss whether dual localization could be achieved by dual targeting and / or by re-localization and try to apprehend the signals required for the respective processes. Finally, we propose that in some instances, dual localized mitochondrial and nuclear proteins might act as retrograde signaling molecules for mitochondrial biogenesis.